Peran Guru Dalam Mengembangkan Literasi di SMK Paskita Global Jakarta Timur - Julinda Siregar; Sahat Simorangkir; Erni Murniarti (CV. Multi Kreasi Media, 2022)
The purpose of this activity is to provide an understanding of literacy through training on how the role of teachers in developing literacy, especially how teachers motivate, inspire and become facilitators for students, make students develop literacy by reading various books and reading books. related to the subject. Resource persons as ABDIMAS implementers carry out activities by providing various materials to Paskita Global Vocational School teachers to be motivated, and become inspirational as well as enthusiastic facilitators in developing student literacy. With the knowledge and insight that teachers get from professional resource persons, namely the abdimas team that provides various materials in developing student literacy, where the teacher becomes the main model that influences students to become literators.